Credit-scoring and bank lending policy in consumer loans. (1st January 2013) - Ganopoulou, Maria; Giapoutzi, Fotini; Kosmidou, Kyriaki; Moysiadis, Theodoros
The objective of this paper is to estimate a credit-scoring model for the consumer loans during the period 2007–2009. A probit model per year is estimated to examine, whether the probability of granting a loan changes through years. Moreover through a bivariate probit model, we analysed how the borrower's characteristics influence the decision of granting consumer loans and their performance. Eventually, we demonstrated that the financial institutions' lending policies are compatible with default risk minimisation and thus it is important for banks to review the borrowers' creditworthiness periodically, in order to minimise default risk.